Howland's isotropic Kts curve for plates with circular holes as a master curve for Kts in orthotropic plates with elliptical holes. (April 2017) - Troyani, Nando; Sánchez, Milagros
The importance of the role played by the so-called stress concentration factors (or symbolically referred to as Kt s) in analysis and design in both mechanical and structural engineering is a well-established fact, and accuracy and ease in their estimation result in significant aspects related to engineering costs, and additionally on both the reliability in the design of parts and/or in the analysis of failed members. In this work, rectangular finite width plates of both isotropic and orthotropic materials with circular and elliptical holes are considered. Based on two key observations reported herein, it is shown in a partially heuristic engineering sense, that Howland's solution curve for the stress concentration factors for finite width plates with circular holes subjected to tension can be viewed as a master curve; accordingly, it can be used as a basis to rather accurately estimate stress concentration factors for isotropic finite width tension rectangular plates with centered elliptical holes and also rather accurately used to estimate stress concentration factors for orthotropic finite width rectangular plates under tension with centered elliptical holes. Two novel concepts are defined and presented to this effect: geometric scaling and material scaling. In all the examined and reported cases, the specific numerical results can be obtained accurately using a hand-held calculator making virtually unnecessary the need to program and/or use other complex programs based on the finite element method, just as an example. The maximum recorded average error for all the considered cases being 2.62% as shown herein.